2017
DOI: 10.17116/jnevro20171171228-42
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of migraine: Recommendations of the Russian experts

Abstract: These recommendations on the diagnosis and treatment of migraine were elaborated by Russian headache experts in accordance with the evidence-based practice. Together with the latest classification, diagnostic principles and criteria of different clinical sub-forms the consensus contains basic data on migraine epidemiology, pathophysiological mechanisms, differential diagnosis and most effective and evidence based approaches to pharmacological and non-pharmacological management of migraine patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 58 publications
0
8
0
4
Order By: Relevance
“…Universal differentiating features for all types of migraine were: predominance of WMH within the frontal lobe and a lower incidence of lesions within the parietal and temporal lobes and their absence within other lobes; equal incidence of juxtacortical and deep location along with less frequent periventricular localization; small (2.5 [1.5; 3] mm) lesion size; the absence of a tendency to merge. Previous studies have reported not only the localization of WMH within frontal, parietal and temporal lobes 9,13,12,18,26,[30][31][32] , but also their infratentorial and occipital location 11,18,30,34 , the involvement of periventricular white matter 6,8,10,13,26 , various sizes of WMH, including con uent lesions 31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Universal differentiating features for all types of migraine were: predominance of WMH within the frontal lobe and a lower incidence of lesions within the parietal and temporal lobes and their absence within other lobes; equal incidence of juxtacortical and deep location along with less frequent periventricular localization; small (2.5 [1.5; 3] mm) lesion size; the absence of a tendency to merge. Previous studies have reported not only the localization of WMH within frontal, parietal and temporal lobes 9,13,12,18,26,[30][31][32] , but also their infratentorial and occipital location 11,18,30,34 , the involvement of periventricular white matter 6,8,10,13,26 , various sizes of WMH, including con uent lesions 31 .…”
Section: Discussionmentioning
confidence: 99%
“…However, recent epidemiological studies have established that in 29-73% of migraine cases, T2 and FLAIR MRI scans reveal white matter hyperintensities (WMH) [4][5][6][7][8] . Most studies demonstrated WMH predominate in migraine with aura 5,6,9,10 and in chronic migraine 11,12 . The high incidence of WMH became one of the reasons to consider migraine as a risk factor for their development 9,11,[13][14][15][16] and highlighted the problem of the diagnostic and prognostic value of WMH in different types of migraine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Перед началом ГБ у пациента могут возникать очаговые неврологические симптомы (мигренозная аура). Возникновению приступа способствуют следующие факторы (триггеры): стресс, нарушения сна или избыточный сон, пищевые продукты (сыр, орехи, шоколад), менструация, яркий свет, укачивание, путешествия, сильные запахи (бензина, духов); часто отмечается провокация приступа употреблением красного вина [12]. Односторонние вегетативные проявления во время боли (слезотечение, покраснение глаза, заложенность уха, носа, ринорея, повышенная потливость, отечность века, миоз, птоз) являются характерными чертами тригеминальных цефалгий [13].…”
Section: первичные и вторичные гб в практике врачаunclassified
“…Профилактическая медикаментозная реабили тация. Имеются определенные различия в осуществлении профилактической медикаментозной реабилитации при хронической мигрени и хронической головной боли напряжения [9][10][11][12][13][14]. В профилактиче-ской реабилитации хронической мигрени большое место занимают некоторые противосудорожные (антипароксизмальные) препараты: препараты вальпроевой кислоты (Депакин) по 600-1500 мг/сут, карбамазепин (Тегретол, Финлепсин) по 400-600 мг/сут, габапентин (Нейронтин, Тебантин) по 300-600 мг 2-3 раза/день, прегабалин (Лирика) по 75-150 мг 2-3 раза/день.…”
Section: медикаментозная реабилитацияunclassified